Free Grace Versus Free Will: John Wesley’s Understanding of Humanity and His practice of Pastoral Guidance - Khoo, Ho Peng (QUAERENS: Journal of Theology and Christianity Studies, 2021)
This is true for John Wesley too. Wesley’s understanding of humanity has not only affected his theological development, especially his Soteriology; it in turn impacted his practice of theology, in particular, his pastoral guidance to the thousands of “Methodists” in the British Isles almost throughout the entire eighteenth century. The latter is particularly true in the light of his concerned with practical Christianity, with the interplay of theology and the realities of daily life